Efficient information theoretic inference for conditional moment restrictions - Richard J. Smith (Centre for Microdata Methods and Practice (cemmap), 2005)
The generalized method of moments estimator may be substantially biased in finite samples, especially so when there are large numbers of unconditional moment conditions. This paper develops a class of first order equivalent semi-parametric efficient estimators and tests for conditional moment restrictions models based on a local or kernel-weighted version of the Cressie-Read power divergence family of discrepancies. This approach is similar in spirit to the empirical likelihood methods of Kitamura, Tripathi and Ahn (2004) and Tripathi and Kitamura (2003). These efficient local methods avoid the necessity of explicit estimation of the conditional Jacobian and variance matrices of the conditional moment restrictions and provide empirical conditional probabilities for the observations.
Keywords: C12; C13; C14; C20; C30; 330; Conditional Moment Restrictions; Local Cressie-Read Minimum Discrepancy; GMM; Semi-Parametric Efficiency; Momentenmethode; Nichtparametrisches Verfahren; Theorie